Efectos del frío en las relaciones hídricas de Quercus ilex en la Serra de Prades (Tarragona) - Sala A.; Picolo R.; Piñol J. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
Daily courses of water potential in Quercus ilex shoots are compared during a winter day in two experimental stations located at the bottom (deeper soils) and at the top (shallow soils) of a watershed in the Serra de Prades (Tarragona, Spain). In each experimental station measures were taken at three canopy levels. A pressure-volume curve analysis was done following the same space sample design. Pre-dawn water potentials are very low indicating that the trees studied were subject to a strong water desiccation. During the day water potential is being recovered reaching a maximum at midday at the top station and in the afternoon at the bottom one. Osmotic potentials are in general very high, and less negative at the top station. This seems to indicate that the solute accumulation was very inactive and that the plants studied are poorly adapted to low temperatures.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)